Universities and Labor Market Mismatch in Kenya - Munene, Ishmael (International Higher Education, 2021)
A nagging policy issue, graduate unemployment in Africa, is a concern among stakeholders. In Kenya, in-built institutional inhibitions and failed reforms explain the mismatch between the labor market and university programs. Some modest reforms and alternative pathways for tertiary education, however, offer a ray of hope.